The status of three species names in the mealybug genus Rastrococcus Ferris (Hemiptera: Coccomorpha: Pseudococcidae) - Williams, Douglas J. (Zootaxa, 2019)
This paper attempts to establish the correct status of three species names in the mealybug genus Rastrococcus Ferris (Hemiptera: Coccomorpha: Pseudococcidae). At present, 31 species are included in the genus (García Morales et al. 2019). The natural distribution of the species is southern Asia and Australasia, but two species have been introduced into Africa and one of them has reached French Guiana.